BAHASA JAWA DIALEK LUMAJANG DI JAWA TIMUR (GEOGRAFI DIALEK) - , APRILIVIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is about âLumajang Javanese Language Dialect in East Java: Geographical Dialectâ This is aimed to find the language symptoms in the phonology area and dialect mapping. This paper uses direct quotation technique and indirect recording method of berian data that consist of 200 Swadesh vocabularies in Lumajang Javanese language dialect. The goal of this combination method is to get more validity and responsible data. This research finds the variety of both phonology and lexical areas. The berian phonetics differences are symbolized by isoglos dashed line while lexical difference is recognized by full isoglos line. These differences are influenced by geographical area where a research is conducted. There are highlands, flatland and coast areas.